Depression, cognitive, and functional outcomes of Problem Adaptation Therapy (PATH) in older adults with major depression and mild cognitive deficits. (8th April 2020) - Kanellopoulos, Dora; Rosenberg, Paul; Ravdin, Lisa D.; Maldonado, Dalynah; Jamil, Nimra; Quinn, Crystal; Kiosses, Dimitris N.
ABSTRACT: Objectives: Antidepressants have limited efficacy in older adults with depression and cognitive impairment, and psychosocial interventions for this population have been inadequately investigated. Problem Adaptation Therapy (PATH) is a psychosocial intervention for older adults with major depression, cognitive impairment, and disability. Design: This study tests the efficacy of PATH versus Supportive Therapy for Cognitively Impaired Older Adults (ST-CI) in reducing depression (Montgamery Asberg Depression Rating Scale [MADRS]) and disability (World Health Organization Disability Assessments Schedule-II [WHODAS-II]) and improving cognitive outcomes (Mini Mental State Examination [MMSE]) over 24 weeks (12 weeks of treatment and 12-week post-treatment follow-up). Setting: Participants were recruited through collaborating community agencies of Weill Cornell Institute of Geriatric Psychiatry. Both interventions and all research assessments were conducted at home. Participants: Thirty-five older adults (age ≥ 65 years) with major depression and cognitive impairment no dementia (CIND). Interventions: PATH aims to increase emotion regulation by incorporating a problem-solving approach, teaching compensatory strategies, and inviting caregiver participation. Supportive Therapy aims to facilitate the expression of affect, as well as promote empathy. Measurements: Depression was measured using the MADRS, disability using the WHODAS-II, and cognition using the MMSE. Results: PATH participants showed significantly greater reduction in MADRS total score (7.04 points at 24 weeks, treatment group by time interaction: F [1, 24.4] = 7.61, p = 0.0108), greater improvement in MMSE total score (2.30 points at 24 weeks, treatment group by time interaction: F [1, 39.8] = 13.31, p = 0.0008), and greater improvement in WHODAS-II total score (2.95 points at 24 weeks, treatment group by time interaction: F [1, 89] = 4.93, p = 0.0290) than ST-CI participants over the 24-week period. Conclusions: PATH participants had better depression, cognitive, and disability outcomes than ST-CI participants over 6 months. PATH may provide relief to depressed older adults with CIND who currently have limited treatment options.